Land use and topographic controls on soil chemical properties in some selected sites of the North West Region of Cameroon - Brenda T. Mbibueh; Reeves M. Fokeng; Valentine A. Tellen; Ivo T. Tawe (Geology, Ecology, and Landscapes)
Land use change affects soil forming processes and modifies site conditioning factors. This paper evaluates land use and topographic controls on soil chemical properties in selected sites of the North West Region of Cameroon. Three topographic zones comprising; low altitude (<1200m), mid-altitude (1200-1500m), and high altitude (˃1500m), under four land use types were studied. 60 soil samples were collected on plots of 30m2, at 0-20cm depth and subjected to chemical analyses. Significant relationships between variables were established via ANOVA and Pearson’s correlation tests. The results revealed significant correlation between soil properties at (P<0.05) and (P<0.01) confident intervals between soil properties with land use and elevation classes. A significant decline (P< 0.01) was observed in the concentrations of pH, Base Saturation (BS), Cation Exchange Capacity (CEC), Total Nitrogen (TN), Soil Organic Carbon (SOC), Soil Organic Matter (SOM), Phosphorus (P) and exchangeable bases in farmlands. Soil chemical properties showed variations across land uses and elevation classes. Soil pH, BS, CEC, SOC, SOM, P, and Ca2+ were statistically significant with topographic variations, while BS, CEC, TN, and Mg2+ varied significantly with land use. Exchangeable potassium (K+) and exchangeable sodium (Na+) showed no significant variations with land use and topographic position.